THE POWER OF EDWARD’S LOVE IN CHRIST WEITZ’S THE TWILIGHT SAGA: NEW MOON MOVIE (2009): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - SARY, DESY PUSPITA (2010)
This research investigates how is the power of Edward’s love in Christ Weitz’s The Twilight Saga: New Moon movie, especially viewed by individual psychological approach. Therefore, the study analyzes the movie in terms of its structural elements and based on the individual psychological perspective. This study belongs to descriptive qualitative study. In this method, the writer uses two data sources; they are primary and secondary data source. The primary data source and the object of the study is the movie The Twilight Saga: New Moon, meanwhile the secondary data sources are any books of literature and psychology related to this study. The writer collects the data from both primary and secondary data sources in a short of document evidence. A result of the analysis shows the following conclusion: first, Christ Weitz wants to deliver message that every people must show the power of love. Second, for shows the power of love achieved by sacrifice will influence the psychological development of the major character. In this movie, Edward Cullen as major character has realized that he must show his power love to reinforce his psychological development.